DUALITY OF NETWORKING AGENCY-STRUCTURES: FEMALE JOURNALISTS IN THE ARENA OF SPORTS MEDIA - Angeliqa, Fitria; Andriani, Fizzy (Selangor Humaniora Review, 2024)
The purpose of this research is to explore how women journalists carry out various social practices in the many sports arenas they encounter, switching from agents to agencies by mobilising their resources. The research draws on Anthony Giddens' structuration theory, which consists of the concepts of agency, structure, resources, and discursive and practical consciousness. Critical construction became its paradigm, with a qualitative research approach. The unit of analysis is an individual, namely women sports news journalists in online media. Data collection techniques with in-depth interviews and observation. The analysis technique used the hermeneutic phenomenological circle of Paul Ricoeur. The results show the descriptions of the various structures that women sports journalists enter. Besides, bring up the agent's identity or agency because of discursive and practical awareness, where the duality aspect appears. Thus, the structuration occurs in the micro-structure and jumping-up to macros (reflects on the text they produced)—but not at the organisational level as a mezzo—reflects women journalists' ability to present themselves as agencies in the arena's structure.